Prevalence and antimicrobial resistance patterns of nontyphoidal Salmonella in Ghana: a systematic review and meta‑analysis - Sarkodie‑Addo. P.; Aglomasa. B.C.; Donkor. E.S. (Tropical Medicine and Health, 2025)
Background Nontyphoidal Salmonella (NTS) is a foodborne pathogen of major public health concern, especially in Sub-Saharan Africa, including Ghana, where it causes invasive infections. However, data on its prevalence, antimi‑ crobial resistance (AMR) patterns, and associated serovars in Ghana are fragmented across multiple studies. Objective This systematic review and meta-analysis aimed to consolidate data on the prevalence, phenotypic and genotypic antimicrobial resistance profles of NTS in Ghana. Methods Following PRISMA guidelines, a systematic search was conducted on August 8, 2024, across four data‑ bases: PubMed, ScienceDirect, Scopus, and Web of Science. A total of 31 studies were included. A random-efects model was used to estimate the pooled prevalence of NTS and the resistance levels of antibiotics reported in two or more studies. Subgroup analysis, multivariate analysis, sensitivity analysis, Egger’s test, and forest plots were per‑ formed to explore variations, assess the infuence of individual studies, test for publication bias, and visualize pooled estimates. Results The pooled prevalence of NTS was estimated at 4.69% (95% CI 2.65–8.16) with high heterogeneity observed among the studies (I2=98.6%, τ2=1.22, τ=1.10, H=8.55, Q=1754.02, p value<0). Prevalence rates fuctu‑ ated over time: 6.27% (2008–2012), 2.09% (2013–2017), and 7.02% (2018–2023), with no signifcant trend observed (Q=2.63, df=2, p value=0.27). Antimicrobial resistance (AMR) rates were high, with resistance to trimethoprim sulfamethoxazole (56.7%), amoxicillin/ampicillin (50.8%), tetracycline (46.7%), and ampicillin (36.2%). Cefotaxime had the lowest resistance at 18.6%. Salmonella Typhimurium was the most identifed serovar (36.7%), followed by S. Enter‑ itidis (7.9%), S. Rubislaw (4.9%), S. Dublin (3.7%), and S. Kentucky (3.6%). Several AMR genes including gyrA, gyrB, qnrB2, and qnrB19 were identifed in human and food samples. Conclusion Despite ongoing interventions, NTS remains a signifcant public health challenge in Ghana, with high AMR levels. The continued rise in resistance to critical antibiotics highlights the need for a One Health approach, improved diagnostics, enhanced surveillance, and targeted public health measures to control NTS and mitigate AMR.
Research Article
Keywords: Nontyphoidal Salmonella; Salmonellosis; Antimicrobial resistance